Investigating the impact of vaccination on COVID-19 dynamics and resurgence risks - Mukhtar, Abdulaziz; Ncube, Esther; Patidar, Kailash (Journal of Innovative Applied Mathematics and Computational Sciences, 2025)
COVID-19 emerged in December 2019 and became a global threat, prompting heightened global surveillance from 2020 to 2022. Although COVID-19 continues to circulate and evolve, global surveillance has substantially reduced. The reduction in surveillance came after the introduction of vaccines worldwide. We formulated a mathematical model to investigate how incorporating vaccines impacts the dynamics of COVID-19 transmission. The study qualitatively analyzed the model and calculated the basic reproduction numbers ($\mathcal{R}_{0}$). We estimated the model's parameters by fitting the model to real COVID-19 case data and using maximum likelihood estimation. To determine which parameters have the greatest impact on the spread and transmission of disease, a sensitivity analysis is carried out. The analysis revealed that the transmission rate $β$ is the most important factor responsible for the spread of COVID-19, while the vaccination rate $ u$ has the most significant impact on controlling the disease. The numerical simulations showed that a high vaccination rate significantly reduces exposed, asymptomatic, symptomatic, and hospitalized individuals, reducing the impact of the virus on the community. It is crucial to consider the rate of immunity loss, as neglecting it could negate the benefits of vaccination.